The Role of Resilience in Managing the Psychological Effects of Infertility Stigma: A Mixed-Methods Study - Jocelyne Annie Houndebasso-Ahoga; Veronica Kaari Makena; Anne Gathoni Wambugu (European Scientific Journal, ESJ, 2026)
Resilience and coping strategies represent major resources for women experiencing infertility, related stigma, and psychological consequences. This study examined how resilience operates in managing psychological distress among women experiencing infertility stigma in evangelical church communities in Zou County, Benin Republic. A convergent mixed-methods design was employed with 384 women, using standardized measures (CD-RISC-10, ISS-SF, DASS-21) alongside focus groups and interviews with 45 church leaders. The quantitative data were analysed using SPSS version 25.0. In a matched mixed-method approach, the qualitative data were converted into quantitative value to enhance analysis. More than a quarter figure of the participants presented with low resilience, the average score on CD-RISC-10 being 24.88 out of 40. ISS-SF significantly predicted DASS-21, infertility stigma accounting for 45% of variance in combined depression, anxiety, and stress. Self-devaluation and social withdrawal revealed primary dimensions. Resilience in moderation analysis yielded significant independent effects on psychological outcomes. Resilience functions as an independent protective factor, providing general psychological resources that improve outcomes regardless of stigma levels, rather than buffering the impact of stigma. Quantitative linear models failed to capture specific context-dependent resilience processes revealed qualitatively. The Stigma-Conscious Framework on Resilience and Posttraumatic Change helped to reframe resilience with inputs and resources specific to the sample. It highlights the importance of integrating context-specific features in the underlying mechanisms to move resilience beyond the concept of general protective factor. Recommendations for practice include interventions targeting self-devaluation and social withdrawal and strengthening culturally embedded resilience resources.